Osteological development and abnormalities of the vertebral column and caudal skeleton in larval and juvenile stages of hatchery reared solea senegalensis (kaup) - Gavaia, Paulo J. (2014)
The Senegal sole is a species recently adapted to aquaculture for which little information on larval development is available. This study was designed to describe normal skeletal development and the occurrence of skeletal malformations in Senegal sole reared in captivity. Eggs were collected from natural spawning, incubated until hatching and larvae reared to the juvenile stage in a closed recirculating system. Samples were collected throughout development at regular intervals from hatching to fully formed juveniles. Specimens were stained with alcian blue and alizarin red and observed for skeletal development and detection of anomalies. A high number of malformations were detected, both in the caudal complex and the vertebral column. About 44% of the individuals observed showed at least one malformation and the highest occurrence of deformities was observed in the caudal region and in the vertebral column. Accordingly, 28% of the total deformities identified in this study were detected at those sites and in adjacent arches and spines. The causes were not identified in this study, but the high incidence of malformations may reflect culture problems due to rearing and/or feeding conditions that affect skeletal development.